(untitled) (Al-Academy, 2026)
The experimental approaches to scenography are one of the most important artistic, intellectual and philosophical processes through which the scenographer or director seeks to create new hypotheses and concepts in innovative artistic ways that seek to enhance the fundamental idea of the theatrical presentation, provide visions that differ from the usual, and call upon other arts and employ them within the context of the theatrical event in an effort to break established patterns and templates. Proposing innovative artistic, aesthetic and intellectual alternatives that work to translate reality using modern methods and audio-visual technical forms, which in turn seek to establish new relationships with the public, create alternative places, and keep pace with scientific and technological development to create distinctive experiences that suit the recipient’s taste and the spirit of the times. The current research included four chapters: The first chapter, the methodological framework. This chapter included the research problem represented by the following question: What is the extent of the influence of experimental approaches in formulating the form and content of the Iraqi theatrical performance, and what are their mechanisms? The importance of the research comes to reveal experimental approaches to scenography in Iraqi theater performances and the mechanism of their operation. The aim of the research is to identify approaches to scenographic experimentation in Iraqi theater performances. The limits of the research are represented by the limits of the topic: it is represented by studying experimental approaches to the scenography of theatrical performances. And temporal limits: theatrical performances for the period (2023). Spatial boundaries: Iraq, Baghdad (National Theater). The chapter concluded by defining the terms linguistically, terminologically, and procedurally. The second chapter includes the theoretical framework, which includes two sections: The first topic: Experimentation, its mechanisms and operation, which is represented by assumptions that differ from the stereotypes, new foundations and concepts, and pragmatic terminology. The second topic: Approaches to scenographic experimentation, represented by the methods and techniques followed by the scenographer, the director, and the work team, with the aim of breaking the constants and summoning various elements to go beyond the prevailing. . Previous studies and discussion. And the indicators resulting from the theoretical framework and previous studies. As for the third chapter, it included the research procedures: (research population, research methodology, research tool, measurement method, analysis unit, and sample analysis), which were chosen in an intentional manner based on the research tool, direct observation, and the measurement method to analyze the chosen model within the descriptive analytical approach, case study or analysis. Content. While the research concluded with the fourth chapter, which included the results and their discussion, then conclusions, recommendations, proposals, a list of sources, appendices, and a summary in English